Analisis Penyebab Getaran Pada Mesin Peniris Minyak Untuk Mencegah Kerusakan Produk Keripik Bayam Milik UMKM Jabal Dinar - Maulana, Adam; Ariyanto, Ariyanto; Yudo, Eko (Manutech : Jurnal Teknologi Manufaktur, 2025)
The oil-draining machine at UMKM Jabal Dinar experienced excessive vibration issues, rendering it inoperative for approximately four years. This problem impacted the quality of the spinach chips produced. This study aims to identify the main causes of unstable vibrations in the oil-draining machine, analyze their effects on product quality, and develop improvement strategies to enhance the machine's vibration stability. The method employed was experimental, with initial vibration measurements reaching 20,83 mm/s, classified in Zone D (red) according to the ISO 10816-3 standard, indicating very high vibrations that could lead to severe damage if not addressed. Modifications were made by replacing the shaft, bearings, and pulleys, as well as performing proper alignment. The improvements resulted in a significant reduction in vibration, positively impacting product quality and extending the machine's lifespan. The study concludes that component modifications and alignment corrections effectively reduced excessive vibrations in the oil-draining machine, ultimately increasing production efficiency and reducing damage to the spinach chips.